A fundamentação das decisões do supremo tribunal federal na presença de “razões de excepcional interesse social” com vistas à modulação dos efeitos na declaração de inconstitucionalidade - Tessari, Cláudio (2021)
The proposal of this thesis is to analyze the exceptional social interest as a requirement for the application of the efeito modulador by the Federal Supreme Court in decisions declaring unconstitutionality, given that, according to the governing legislation of the matter (arts. 27 of Law n. 9,868 /1999; 11 of Law n. 9,882/1999 and 927, § 3, of the Code of Civil Procedure), there is an open and indefinite legal concept regarding the exceptional social interest. As a result of this circumstance, the use of the state interest (public) is frequently seen in these decisions as a synonym for exceptional social interest (without motivation), especially when the consequentialist argument is used. The situation is wrong and can be resolved with mandatory reasons as determined by the Code of Civil Procedure and the Federal Constitution, demonstrating that procedural guarantees are also an extremely important legal instrument of social protection for the control of public power activities since the State executes the public interests and must defend the social interests. Based on these premises, it will be demonstrated that the need to set parameters is imperative for defining the reasons of exceptional social interest in the decisions of unconstitutionality handed down by the Federal Supreme Court when there is use of the institute of efeito modulador.